Identifying beliefs underlying pre-drivers' intentions to take risks: An application of the Theory of Planned Behaviour. (April 2016) - Rowe, Richard; Andrews, Elizabeth; Harris, Peter R.; Armitage, Christopher J.; McKenna, Frank P.; Norman, Paul
Highlights: Risky driving such as speeding puts novices at crash risk. There is growing evidence that novice risk-taking has its roots in pre-driving. We use the Theory of Planned Behaviour to identify the pre-driver beliefs behind risky intentions. Advantages and disadvantages of risk-taking were highlighted. The identified beliefs may form the basis of pre-driver road safety interventions. Abstract: Novice motorists are at high crash risk during the first few months of driving. Risky behaviours such as speeding and driving while distracted are well-documented contributors to crash risk during this period. To reduce this public health burden, effective road safety interventions need to target the pre-driving period. We use the Theory of Planned Behaviour (TPB) to identify the pre-driver beliefs underlying intentions to drive over the speed limit ( N  = 77), and while over the legal alcohol limit ( N  = 72), talking on a hand-held mobile phone ( N  = 77) and feeling very tired ( N  = 68). The TPB explained between 41% and 69% of the variance in intentions to perform these behaviours. Attitudes were strong predictors of intentions for all behaviours. Subjective norms and perceived behavioural control were significant, though weaker, independent predictors of speeding and mobile phone use. Behavioural beliefs underlying these attitudes could be separated into those reflecting perceived disadvantages (e.g., speeding increases my risk of crash) and advantages (e.g., speeding gives me a thrill). Interventions that can make these beliefs safer in pre-drivers may reduce crash risk once independent driving has begun.